The Relationship between Implementation Principles of Implementation with Organizational Accelerations, Ethical Leadership and Empowerment of Managers (Case study: Employees of national banks in Sari, District 1) - Maryam Taghvaee yazdi; Jalal Abdi; Mohammad Taghipour (Allameh Tabataba'i University Press, 2018)
The purpose of this study was to investigate "the relationship between implementation factors of successor with organizational growth, ethical leadership and empowerment of managers of national banks in Sari city from the employees' point of view". Statistical population is all employees of National Banks of Sari District 1. The sample size is 187 persons. The method of data collection has been two methods, Data gathering tool was four questionnaires of Substitute Worker Mattiqi et al. (2009), Speedsweed Organizational Accelerating Inventory (2007), Brown's Leadership Questionnaire (2005) and Managers Empowerment Questionnaire (Kordnaeich, 2010). Data analysis in the descriptive findings section examines the position of each information about them in the form of tables and charts, and in the inferential findings of the Spearman correlation test And Pearson and t test through SPSS19 software. The results of the research showed that there is a significant and direct relationship between the factors of implementation of the successor and the organizational progress of the managers of the national banks. However, there are no significant relationships between the implementation of the successor of the managers with the ethical leadership and the empowerment of the managers of the national banks the employees' point of view.